The Influence of the Problem Based Learning (PBL) Model on Learning Outcomes in Social Sciences Subjects ASEAN Class VIII UPTD SMP NEGERI 7 PEMATANG SIANTAR - Olly Yohana Simatupang; Benjamin Simamora; Debbi Petra Meyana Sitorus (International Journal of Global Sustainable Research, 2023)
This research aims to learn about the improvement of learning outcomes of ASEAN material IPS classes VIII UPTD SME State 7 Siantar Year Students by applying the learning model Problem Based Learning (PBL). This research uses a quantitative approach. This type of research is a quasi-experimental research carried out in the 7th Pematang Siantar State High School. The research population is the whole of the students of the eighth grade in the state high school 7 Pematang Siantar with a total of 224 students and the subject of this research is the classes VIII-2 and VIII-3 which totaled 64 people. While for technical data analysis used are Normality Test, Homogenity Test as well as Independent Samples Test using SPSS Version 21. Based on the results of data analysis using Independent Sample Test, thitung= 2.928 and ttable (at a significant level of 5%)= 1.699 means thitung > ttable. According to the criteria, H0 is accepted if thitung < ttable and H0 rejected if Thitung > tab. Thus, it can be concluded that there is an influence of the Problem Based Learning (PBL) Model on learning outcomes on the ASEAN Class VIII UPTD High School Students' Lectures.